Method for preparing short-channel transistor by mechanically stacking electrodes

Through the mechanical stacking electrode method, the problems of high cost and material damage risk in EBL technology are solved, and the efficient and low-cost preparation of short-channel devices are achieved, the stability and transparency of materials are improved, and the manufacturing process is simplified.

CN119325247AActive Publication Date: 2025-01-17UNIV OF SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411316834.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-17
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

In the prior art, the preparation methods of short-channel devices such as EBL technology have problems such as high equipment and operational costs, high material damage risk, long manufacturing cycles, and unstable performance of transparent polypropylene resins.

Method used

By using the mechanical stacking electrode method, by preparing electrodes on the substrate layer, setting an adhesion layer and supporting layer, peeling off the composite architecture layer, transferring the electrode material to the target carrier, using modified polypropylene resin to enhance transparency and wear resistance, reducing the preparation cost and Risk of material damage.

Benefits of technology

It significantly reduces the preparation cost, avoids radiation damage to the material by high-energy electron beams, improves the stability and transparency of the material, simplifies the manufacturing process, and enhances process flexibility and customization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325247A_ABST
    Figure CN119325247A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a short-channel transistor by mechanically stacking electrodes, belongs to the technical field of transistor processing, and is used for solving the technical problems of economization of a short-channel electrode preparation method in the prior art and to further improve the performance of traditional transparent polypropylene resin. The method comprises the following steps of: preparing a plurality of electrodes on the surface of a substrate layer subjected to cleaning treatment by combining the preparation of modified polypropylene resin with the method for preparing the short-channel transistor by mechanically stacking the electrodes provided by the invention; the high transparency and scratch resistance of the modified polypropylene resin guarantee the accuracy of mechanical stacking, the excellent leveling performance, high temperature resistance and adhesion performance of the modified polypropylene resin guarantee the stability of the electrode structure in the transfer process, the preparation cost of the short-channel transistor is reduced through cooperation of the modified polypropylene resin and the electrode structure, and the accuracy of the short-channel transistor is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of transistor processing, and in particular to a method for preparing a short channel transistor by mechanically stacking electrodes. Background Art

[0002] With the continuous exploration of new materials and new structures, short channel devices have become important in laboratory research. Short channel devices not only promote the in-depth research of basic science, but also are an important means to build high-performance integrated devices. By reducing the channel length, short channel devices reduce the transmission time of carriers and effectively reduce the power consumption of the device. At present, extreme ultraviolet lithography and electron beam lithography are the mainstream preparation methods. The required electrode pattern is defined on a silicon wafer coated with sensitive materials by using an extreme ultraviolet light source or a focused electron beam. Among them, electron beam lithography technology has become the first choice for the preparation of short channel devices with its high resolution and flexibility.

[0003] In the prior art, the EBL technology is applied to the preparation process of short channel devices, which includes the following steps: first, a substrate with a flat surface is selected for cleaning to eliminate surface impurities; then, a layer of electron beam photoresist is evenly spin-coated on the surface of the substrate, and pre-baked to improve the adhesion of the photoresist and remove the solvent; then, an electron beam lithography machine is used to accurately expose the photoresist according to a preset pattern to change its dissolution rate. The exposure dose and the focusing accuracy of the electron beam directly affect the fineness of the short channel. The exposed substrate is then placed in a developer to remove the photoresist in the exposed part to form a desired pattern, and then electrode materials are deposited on the patterned photoresist by physical vapor deposition technology; finally, the remaining photoresist and the electrode material on the upper layer are removed, leaving only the desired electrode pattern.

[0004] In the production of short-channel devices, ultraviolet lithography and electron beam lithography are common manufacturing processes. Although EBL technology is very important in pushing the limits of micro-nano size, high equipment and operating costs limit its widespread application. EBL technology is a key link in micro-nano manufacturing, but its high equipment cost and the requirements for environmental control and precise equipment adjustment increase operating costs. In addition to the cost of the equipment itself, it also involves high reservation machine time fees and machine maintenance costs, which limit its popularization in the manufacture of short-channel devices. The time cycle of existing technologies is long, and the EBL process involves complex reservation waiting and processing time.

[0005] The photolithography process requires tedious steps such as vacuum processing, focusing, calibration and positioning, which significantly prolong the manufacturing cycle and increase time costs. The existing technology has a high risk of material damage. The direct interaction between the electron beam and the material in the EBL technology may cause charge accumulation and radiation damage, which will affect the performance and reliability of the device.

[0006] Traditional transparent polypropylene resins, such as polymethyl methacrylate, have excellent optical properties, which can reach more than 92.0%, but they are very susceptible to scratches. The scratches produced by scratches will significantly affect their transparency, making it unable to provide clear visual effects. At the same time, polymethyl methacrylate is extremely unstable when heated, resulting in unstable performance as an adhesive material.

[0007] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0008] The object of the present invention is to provide a method for preparing a short channel transistor by mechanically stacking electrodes, so as to solve the technical problems of the economical preparation method of the short channel electrode in the prior art and the need to further improve the performance of the traditional transparent polypropylene resin.

[0009] The object of the present invention can be achieved by the following technical solution: A method for preparing a short channel transistor by mechanically stacking electrodes, comprising the following steps:

[0010] S1. Preparing a plurality of electrodes on the surface of the substrate layer after cleaning treatment;

[0011] S2, arranging an adhesion layer and a support layer on the substrate layer and the electrode to obtain a substrate layer modified with a composite framework layer;

[0012] S3, peeling the composite structure from the substrate layer, and post-processing to obtain a plurality of electrode materials;

[0013] S4, selecting the desired electrode material and transferring it to the surface of the target carrier, and post-processing to obtain the transistor material;

[0014] S5. Continue to select the desired electrode material prepared in steps S1-S3 and transfer it to the surface of the target carrier to obtain a short channel transistor.

[0015] Furthermore, the substrate layer includes a single silicon wafer, mica, a flexible substrate, silicon nitride, silicon oxide and graphene.

[0016] Furthermore, in step S1, the cleaning process includes: using acetone, isopropyl alcohol and deionized water to clean the substrate layer in sequence for 3-5 times.

[0017] Furthermore, the operation of preparing the electrode includes determining the electrode shape and forming the electrode entity. The method of determining the electrode shape includes ultraviolet lithography, electron beam lithography, hard mask and nanosphere lithography; the method of forming the electrode entity includes electron beam evaporation coating, thermal evaporation coating, magnetron sputtering coating and electrochemical deposition.

[0018] Preferably, the method for determining the electrode shape is electron beam lithography, and the method for forming the electrode entity is thermal evaporation coating.

[0019] Further, in step S1, the electrode is processed by the following steps:

[0020] A1. After spin coating a negative photoresist on the substrate layer, the substrate layer is transferred to a drying oven at a temperature of 80° C. for vacuum drying to obtain a substrate layer with a negative photoresist attached to the surface;

[0021] A2. After adjusting the shape of the radiation area of ​​the photolithography machine, the photoresist is subjected to radiation exposure treatment to obtain a plurality of patterned photoresist surfaces of desired shapes;

[0022] A3. Electron beam evaporation technology is used to perform surface deposition on the patterned photoresist surface. After deposition, the remaining photoresist is stripped off to obtain an electrode.

[0023] Furthermore, the shape of the electrode to be transferred can be arbitrarily selected according to requirements, and the material of the electrode to be transferred includes gold, silver, copper, aluminum, bismuth, target and platinum.

[0024] Furthermore, in step S2, the method for forming the adhesive layer and the support layer includes the following steps:

[0025] B1. Spin-coat the adhesive solution on the surface of the substrate layer to cover all the electrodes, then transfer the material to a drying oven at 80°C for vacuum drying and keep warm for 20-40 minutes to obtain a substrate layer with an adhesive layer attached to the surface;

[0026] B2. Use a thin plate as a support layer to adhere the adhesive layer, transfer the material to a drying oven, increase the temperature of the drying oven to 50°C, and keep it warm for 10-15 minutes to further obtain a composite structure layer consisting of an electrode / adhesion layer / support layer.

[0027] Furthermore, in step B1, the adhesive solution is an acetone solution of 15-30 wt % modified polypropylene resin; in step B2, the thin plate includes a polydimethylsiloxane thin plate and a polydimethylsiloxane / polyvinyl chloride thin plate, and the thickness of the thin plate is 200-250 μm.

[0028] Furthermore, the preparation method of the modified polypropylene resin is as follows: 3-5 parts of 3-isocyanatepropyltrimethoxysilane, 8-10 parts of modified polypropylene resin precursor, 0.3-0.5 parts of triethylamine and 30-40 parts of dimethyl sulfoxide are weighed by weight and added into a reaction kettle, reacted at room temperature for 2-4 hours, and post-treated to obtain the modified polypropylene resin.

[0029] The reaction equation for preparing modified polypropylene resin is:

[0030]

[0031] Where:

[0032] The reaction principle for preparing modified polypropylene resin is as follows: under weakly alkaline conditions, the ethoxy group of 3-isocyanatepropyltrimethoxysilane is hydrolyzed to generate a silanol group, which reacts with the hydroxyl group of the modified polypropylene resin precursor to form a silicon-oxygen bond to prepare the modified polypropylene resin.

[0033] Furthermore, the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100° C., and the reaction liquid is distilled under reduced pressure until no liquid is extracted to obtain a modified polypropylene resin.

[0034] Furthermore, the preparation method of the modified polypropylene resin precursor is as follows: 3-5 parts of methyl methacrylate, 5-8 parts of 2-hydroxypropyl-1,2-phthalic acid-2-[(2-methyl-1-oxo-2-propenyl)oxy]ethyl ester, 0.3-0.5 parts of azobisisobutyronitrile and 30-40 parts of dimethyl sulfoxide are weighed by weight and added into a reactor, the temperature of the reactor is increased to 50-70° C., the reaction is kept warm for 2-4 hours, and the modified polypropylene resin precursor is obtained by post-treatment.

[0035] The reaction equation for preparing modified polypropylene resin precursor is:

[0036]

[0037] Where:

[0038] The reaction principle for preparing the modified polypropylene resin precursor is as follows: under the action of azobisisobutyronitrile as a free radical initiator, methyl methacrylate and 5-8 parts of 2-hydroxypropyl-1,2-phthalic acid-2-[(2-methyl-1-oxo-2-propenyl)oxy]ethyl ester undergo free radical polymerization to finally generate a modified polypropylene resin precursor.

[0039] Furthermore, the post-treatment includes: after the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80-100° C., and the reaction liquid is distilled under reduced pressure until no liquid is extracted to obtain a modified polypropylene resin precursor.

[0040] Furthermore, in step S3, the composite structure layer is peeled off by using chemical reagents to flush the connection between the adhesive layer and the substrate layer, using tweezers to clamp the composite structure layer and the substrate layer respectively, and slowly lifting the composite structure layer until it is completely peeled off from the substrate layer.

[0041] Furthermore, in step C2, the chemical reagents include acetone solution, isopropanol solution, saturated hydrogen peroxide solution and saturated sodium hydroxide solution.

[0042] Furthermore, in step S3, the post-processing operation includes: using a cutting machine to cut the composite structure into a desired shape, separating a plurality of electrodes, and obtaining a plurality of electrode materials consisting of a desired electrode / adhesion layer / support layer.

[0043] Furthermore, in step S4, the method for transferring the electrode material is as follows: attach one side of the support layer of a desired electrode material to a glass sheet, use a transfer table to bond the laminated structure to a target carrier, apply a pressure of 200-400 Pa in the bonding state, and heat to 120-150°C for 5-10 minutes to obtain a target carrier modified with the electrode material.

[0044] Furthermore, in step S4, the post-processing operation includes: transferring the target carrier modified with the electrode material to a solvent solution and soaking it for 5-10 minutes, peeling off the adhesion layer and the support layer to obtain a laminated structure consisting of an electrode / target carrier, placing the laminated structure in an annealing machine, setting the annealing machine temperature to 150-170°C, and setting the annealing time to 1-3 hours to obtain a short channel transistor precursor.

[0045] Furthermore, in step S4, the dissolving solution is acetone.

[0046] Furthermore, the target carrier includes a rigid carrier and a flexible carrier, the rigid carrier includes silicon oxide, single crystal silicon and diamond; the flexible carrier includes polydimethylsiloxane.

[0047] Optionally, the target carrier surface has a prefabricated thin layer structure, and the thin layer structure includes a metal electrode, a metal antenna, and a two-dimensional material.

[0048] Further, in step S5, the short channel transistor is processed by the following steps:

[0049] D1. Select a desired electrode material from the remaining electrode materials prepared in steps S1-S3, attach one side of the support layer of the desired electrode material to the glass sheet, position it just above the short channel transistor precursor, and precisely adjust the Z-axis height of the transfer table to ensure consistency of the distance between the short channel transistor precursor and the desired electrode material;

[0050] D2. Adjust the position of the transfer table in the x- and y-axis directions to control the distance between the two electrodes of the required electrode material and the short-channel transistor precursor. When the distance reaches the requirement, use the transfer table to accurately fit the required electrode material to the target carrier. Apply a pressure of 300-500 Pa to the new composite architecture layer in the fitted state, and heat it to 100-150°C for 5-10 minutes. During the process, use a laser interferometer to measure the distance and angle between the required electrode material and the short-channel transistor precursor to obtain a modified short-channel transistor precursor.

[0051] D3. Soak the modified short channel transistor precursor in the dissolving solution for 5-10 minutes. After peeling off the adhesion layer and the supporting layer, put the material into an annealing machine. The annealing machine temperature is set to 150-170°C and the annealing time is set to 1-3 hours to obtain a short channel transistor.

[0052] Furthermore, in step D3, the dissolving liquid is acetone.

[0053] Optionally, the short channel transistor is cleaned with a chemical reagent or an acid-base solution to remove the adhesion layer residue.

[0054] Optionally, the chemical reagent includes acetone, isopropanol, or ethanol.

[0055] Optionally, the short channel transistor is cleaned using plasma to remove adhesion layer residues.

[0056] Optionally, steps S1-S3 can prepare a number of electrode materials according to demand, and collect them for later use after cutting.

[0057] Optionally, steps S4-S5 are repeatedly performed on the same target carrier, so that a variety of combinations of short channel structures can be obtained on the same target carrier.

[0058] The present invention has the following beneficial effects:

[0059] 1. The present invention provides a method for preparing a short channel transistor by mechanically stacking electrodes, which significantly reduces the preparation cost compared with the traditional EBL technology. The EBL equipment is not only expensive in terms of equipment investment and maintenance, but also has high operating costs due to its complex operation and specific consumables (such as electron beam photoresist); the present method provides a more cost-effective solution by simplifying the process and reducing the demand for special materials, as well as weak dependence on high-precision instruments, and significantly reduces the preparation cost compared with electron beam lithography, including equipment investment and maintenance costs, as well as operation running costs; the simplified preparation process and reduced demand for special materials further reduce the marginal cost of the experiment, so that laboratories with limited budgets can also conduct high-precision device preparation research.

[0060] 2. The present invention provides a method for preparing a short channel transistor by mechanically stacking electrodes. Compared with the traditional EBL technology, the present invention effectively avoids direct contact between the target carrier and potential pollution sources such as photoresist and developer by prefabricating electrodes on the substrate layer and then transferring them to the target carrier, thereby reducing the risk of contamination of the target carrier. The traditional EBL technology prepares short channel electrodes by directly acting a high-energy electron beam on the target carrier. The high-energy electron beam may cause charge accumulation of the sample when interacting with the sample. The high-energy electron beam may also cause radiation damage to the material, affecting the device performance. The secondary stacking preparation method avoids the radiation damage that may be caused by the high-energy electron beam to the material, protects the original properties of the material, and the reduction in material damage not only helps to protect precious or sensitive research samples, but also reduces the laboratory's dependence on special processing facilities. At the same time, on the same target carrier, repeated stacking can be performed according to needs to obtain a combination structure of multiple short channel electrodes. This high degree of process flexibility not only makes a variety of device configurations possible, but also further enhances the customizability and adaptability of production to meet diverse application needs.

[0061] 3. The present invention synthesizes a modified polypropylene resin precursor having a large number of ester bonds and benzene rings by utilizing free radical polymerization reaction. The large number of ester groups inside the modified polypropylene resin precursor enhances the transparency of the modified polypropylene resin precursor, and the presence of the benzene ring enhances the rigidity of the modified polypropylene resin precursor, further enhancing its wear resistance, reducing scratches caused by wear between the modified polypropylene resin precursor and the equipment, making its transparency more stable; the modified polypropylene resin is obtained by introducing siloxane through cross-linking with a silane coupling agent, and while enhancing its cross-linking ability with inorganic materials, its leveling performance and high temperature resistance are significantly enhanced, and its adhesion with the organic film is enhanced, and its surface is flat so that the organic film remains flat, enhancing its adhesion with the support layer, and ensuring the stability of the composite structure layer; the high-transparency modified polypropylene resin prepared by the present invention cooperates with the high-precision transfer platform, and the high transparency ensures that the transfer platform accurately controls the electrode channels, while ensuring the accuracy of the relative positions between the electrode materials, ensuring the control of the device size, and at the same time, avoiding direct contact between the electrode and the support layer and other potential pollution sources, effectively reducing the pollution risk in the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0063] Figure 1 The figure is a flow chart of the preparation of the short channel electrode of the present invention.

[0064] Figure 2 A schematic diagram of making several electrodes on the surface of the substrate layer.

[0065] Figure 3 A schematic diagram of providing an adhesion layer and a support layer on a substrate layer and an electrode surface;

[0066] Figure 4 A schematic diagram of peeling a composite structure layer from a substrate layer;

[0067] Figure 5 A schematic diagram of cutting the composite framework layer into the desired electrode material;

[0068] Figure 6 Schematic diagram of transferring the desired electrode material to the target carrier;

[0069] Figure 7 A schematic diagram of peeling off the adhesive layer and the support layer;

[0070] Figure 8 Schematic diagram of transferring the desired electrode material to the target carrier;

[0071] Fig. 9 Schematic diagram of adjusting the transfer stage parameters to align the repeatedly prepared composite architecture layer with the transferred electrode to obtain a channel that meets the requirements;

[0072] Fig.10 Schematic diagram of the side and top views of the short channel electrode tube after the transfer is completed.

[0073] In the figure: 1, substrate layer; 2, electrode; 3, adhesion layer; 4, support layer; 5, target carrier. DETAILED DESCRIPTION

[0074] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0075] Example 1

[0076] This embodiment is used to provide a method for preparing a short channel transistor by mechanically stacking electrodes, comprising the following steps:

[0077] S1. Preparation of adhesive solution

[0078] 9.0 g of methyl methacrylate, 18.0 g of 2-hydroxypropyl-1,2-phthalic acid-2-[(2-methyl-1-oxo-2-propenyl)oxy]ethyl ester, 1.2 g of azobisisobutyronitrile and 96.0 g of dimethyl sulfoxide were weighed and added to a reactor. The temperature of the reactor was raised to 50° C. and the reaction was kept warm for 2 h. After the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid was produced, to obtain 26.6 g of a modified polypropylene resin precursor;

[0079] Weigh 8.0 g of 3-isocyanatepropyltrimethoxysilane, 24.0 g of modified polypropylene resin precursor, 1.1 g of triethylamine and 96.0 g of dimethyl sulfoxide into a reactor, react at room temperature for 2-4 h, and after the reactor is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain 31.2 g of modified polypropylene resin;

[0080] 15.0 g of modified polypropylene resin and 85.0 g of acetone were weighed and added into a reaction kettle and mixed evenly to obtain an acetone solution of 15.0 wt % modified polypropylene resin.

[0081] S2. Preparation of composite architecture layer

[0082] Rinse silicon nitride 1 with acetone, isopropanol, and deionized water three times in sequence;

[0083] After spin coating the photoresist on the cleaned silicon nitride 1, the silicon nitride 1 is placed in a drying oven at 80° C. for vacuum drying for 20 minutes to obtain the silicon nitride 1 with the surface modified with the photoresist;

[0084] After adjusting the shape of the radiation area of ​​the photolithography machine, the photoresist is subjected to radiation exposure treatment to obtain a plurality of patterned photoresist surfaces of desired shapes;

[0085] Using thermal evaporation coating technology to deposit silver electrodes on the surface of the patterned photoresist to obtain a plurality of patterned electrodes 2, and then peeling off the photoresist to obtain a plurality of silicon nitride 1 modified with the electrodes 2;

[0086] After spin coating the surface of silicon nitride 1 with 15.0 wt % modified polypropylene resin in acetone solution to coat electrode 2, silicon nitride 1 / electrode 2 was placed in a drying oven at 80° C. for vacuum drying for 20 min to obtain an adhesion layer 3;

[0087] A polydimethylsiloxane sheet with a thickness of 200 μm is used as a support layer 4 to adhere to the adhesive layer 3, and the material is transferred to a drying oven. The temperature of the drying oven is increased to 50° C. and kept warm for 10 minutes to obtain a silicon nitride 1 modified by a composite structure layer consisting of an electrode 2 / adhesion layer 3 / support layer 4;

[0088] The connection between the adhesion layer 3 and the silicon nitride 1 is washed with an acetone solution, and the composite architecture layer and the silicon nitride 1 are clamped with tweezers respectively, and the composite architecture layer is slowly lifted up until it is completely separated from the silicon nitride 1 to obtain the composite architecture layer.

[0089] S3. Preparation of short channel electrode tube

[0090] After the composite framework layer is cut into several required electrode materials, they are collected for later use, and a required electrode material is selected and one side of its support layer 4 is attached to a glass sheet, and the required electrode material is attached to the single crystal silicon 5 using a transfer table, and a pressure of 200 Pa is applied in the attached state, and the electrode material is heated to 120° C. and maintained for 5 minutes to obtain a target carrier modified with the electrode material;

[0091] The target carrier 5 modified with the electrode material is transferred to a solvent solution and soaked for 5 minutes. After peeling off the adhesion layer 3 and the support layer 4, a laminated structure consisting of the electrode 2 / target carrier 5 is obtained. The laminated structure is placed in an annealing machine, the annealing machine temperature is set to 150° C., and the annealing time is set to 1 hour to obtain a short channel transistor precursor;

[0092] Selecting a desired electrode material from the remaining electrode materials prepared in steps S1-S2;

[0093] Attach one side of the support layer 4 of the required electrode material to the glass sheet, position it just above the short-channel transistor precursor, and ensure the consistency of the distance between the required electrode material and the short-channel transistor precursor by accurately adjusting the Z-axis height of the transfer table;

[0094] The position of the transfer table in the x-axis and y-axis directions is adjusted to control the distance between the two electrodes of the required electrode material and the short-channel transistor precursor. When the distance reaches the requirement, the required electrode material is precisely bonded to the single crystal silicon 5 by using the transfer table. In the bonded state, a pressure of 300 Pa is applied to the new composite architecture layer, and it is heated to 100° C. and maintained for 5 minutes. During the process, a laser interferometer is used to measure and adjust the distance and angle between the required electrode material and the short-channel transistor precursor to obtain a modified short-channel transistor precursor.

[0095] The modified short channel transistor precursor is immersed in a dissolving solution for 5-10 minutes. After peeling off the adhesion layer 3 and the support layer 4, the material is placed in an annealing machine. The annealing machine temperature is set to 150° C. and the annealing time is set to 1 hour to obtain a short channel transistor.

[0096] Example 2

[0097] This embodiment is used to provide a method for preparing a short channel transistor by mechanically stacking electrodes, comprising the following steps:

[0098] S1. Preparation of adhesive solution

[0099] 7.5 g of methyl methacrylate, 17.5 g of 2-hydroxypropyl-1,2-phthalic acid-2-[(2-methyl-1-oxo-2-propenyl)oxy]ethyl ester, 1.2 g of azobisisobutyronitrile and 80.0 g of dimethyl sulfoxide were weighed by weight and added to a reactor. The temperature of the reactor was raised to 70° C. and the reaction was kept warm for 4 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 100° C. and distilled under reduced pressure until no liquid was produced, to obtain 24.3 g of a modified polypropylene resin precursor;

[0100] 10.6 g of 3-isocyanatepropyltrimethoxysilane, 21.4 g of modified polypropylene resin precursor, 1.2 g of triethylamine and 96.0 g of dimethyl sulfoxide were weighed by weight and added to a reactor, and reacted at room temperature for 2-4 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 100° C., and distilled under reduced pressure until no liquid was produced, to obtain 31.5 g of modified polypropylene resin;

[0101] 30.0 g of modified polypropylene resin and 70.0 g of acetone were weighed and added into a reaction kettle and mixed evenly to obtain an acetone solution of 30.0 wt % of modified polypropylene resin.

[0102] S2. Preparation of composite architecture layer

[0103] The silicon nitride 1 is rinsed with acetone, isopropanol and deionized water five times in sequence;

[0104] After spin coating the photoresist on the cleaned silicon nitride 1, the silicon nitride 1 is placed in a drying oven at 80° C. for vacuum drying for 40 minutes to obtain the silicon nitride 1 with the surface modified with the photoresist;

[0105] After adjusting the shape of the radiation area of ​​the photolithography machine, the photoresist is subjected to radiation exposure treatment to obtain a plurality of patterned photoresist surfaces of desired shapes;

[0106] Using thermal evaporation coating technology to deposit silver electrodes on the surface of the patterned photoresist to obtain a plurality of patterned electrodes 2, and then peeling off the photoresist to obtain a plurality of silicon nitride 1 modified with the electrodes 2;

[0107] After spin coating the surface of silicon nitride 1 with 30.0 wt% modified polypropylene resin in acetone solution to coat electrode 2, silicon nitride 1 / electrode 2 was placed in a drying oven at 80° C. for vacuum drying for 40 min to obtain an adhesion layer 3;

[0108] A polydimethylsiloxane sheet with a thickness of 250 μm is used as a support layer 4 to adhere to the adhesive layer 3, and the material is transferred to a drying oven. The temperature of the drying oven is increased to 50° C. and kept warm for 15 minutes to obtain a silicon nitride 1 modified by a composite structure layer consisting of an electrode 2 / adhesion layer 3 / support layer 4;

[0109] The connection between the adhesion layer 3 and the silicon nitride 1 is washed with an acetone solution, and the composite architecture layer and the silicon nitride 1 are clamped with tweezers respectively, and the composite architecture layer is slowly lifted up until it is completely separated from the silicon nitride 1 to obtain the composite architecture layer.

[0110] S3. Preparation of short channel electrode tube

[0111] After the composite framework layer is cut into several required electrode materials, they are collected for later use, and a required electrode material is selected and one side of its support layer 4 is attached to a glass sheet, and the required electrode material is attached to the single crystal silicon 5 using a transfer table, and a pressure of 400 Pa is applied in the attached state, and the electrode material is heated to 150° C. and maintained for 10 minutes to obtain a target carrier modified with the electrode material;

[0112] The target carrier 5 modified with the electrode material is transferred to a solvent solution and soaked for 10 minutes. After peeling off the adhesion layer 3 and the support layer 4, a laminated structure consisting of the electrode 2 / target carrier 5 is obtained. The laminated structure is placed in an annealing machine, the annealing machine temperature is set to 170°C, and the annealing time is set to 3 hours to obtain a short channel transistor precursor;

[0113] Selecting a desired electrode material from the remaining electrode materials prepared in steps S1-S2;

[0114] Attach one side of the support layer 4 of the required electrode material to the glass sheet, position it just above the short-channel transistor precursor, and ensure the consistency of the distance between the required electrode material and the short-channel transistor precursor by accurately adjusting the Z-axis height of the transfer table;

[0115] The position of the transfer table in the x-axis and y-axis directions is adjusted to control the distance between the two electrodes of the required electrode material and the short-channel transistor precursor. When the distance reaches the requirement, the required electrode material is precisely bonded to the single crystal silicon 5 by using the transfer table. In the bonded state, a pressure of 300 Pa is applied to the new composite architecture layer, and it is heated to 100° C. and maintained for 5 minutes. During the process, a laser interferometer is used to measure and adjust the distance and angle between the required electrode material and the short-channel transistor precursor to obtain a modified short-channel transistor precursor.

[0116] The modified short channel transistor precursor was immersed in a dissolving solution for 10 minutes. After peeling off the adhesion layer 3 and the support layer 4, the material was placed in an annealing machine. The annealing machine temperature was set to 170° C. and the annealing time was set to 3 hours to obtain a short channel transistor.

[0117] Example 3

[0118] This embodiment is used to provide a method for preparing a short channel transistor by mechanically stacking electrodes, comprising the following steps:

[0119] S1. Preparation of adhesive solution

[0120] 10.0 g of methyl methacrylate, 14.0 g of 2-hydroxypropyl-1,2-phthalic acid-2-[(2-methyl-1-oxo-2-propenyl)oxy]ethyl ester, 1.0 g of azobisisobutyronitrile and 70.0 g of dimethyl sulfoxide were weighed by weight and added to a reactor. The temperature of the reactor was raised to 60° C. and the reaction was kept warm for 3 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 90° C. and distilled under reduced pressure until no liquid was produced, to obtain 23.5 g of a modified polypropylene resin precursor;

[0121] 11.4 g of 3-isocyanatepropyltrimethoxysilane, 20.6 g of modified polypropylene resin precursor, 1.0 g of triethylamine and 84.0 g of dimethyl sulfoxide were weighed by weight and added to a reactor, and reacted at room temperature for 2-4 hours. After the reactor was cooled to room temperature, the reaction liquid was added to a rotary evaporator with a water bath temperature of 90° C., and distilled under reduced pressure until no liquid was produced, to obtain 31.5 g of modified polypropylene resin;

[0122] 20.0 g of modified polypropylene resin and 80.0 g of acetone were weighed and added into a reaction kettle and mixed evenly to obtain an acetone solution of 20.0 wt % of modified polypropylene resin.

[0123] S2. Preparation of composite architecture layer

[0124] The silicon nitride 1 is rinsed with acetone, isopropanol and deionized water four times in sequence;

[0125] After spin coating the photoresist on the cleaned silicon nitride 1, the silicon nitride 1 is placed in a drying oven at 80° C. for vacuum drying for 30 minutes to obtain the silicon nitride 1 with the surface modified with the photoresist;

[0126] After adjusting the shape of the radiation area of ​​the photolithography machine, the photoresist is subjected to radiation exposure treatment to obtain a plurality of patterned photoresist surfaces of desired shapes;

[0127] Using thermal evaporation coating technology to deposit silver electrodes on the surface of the patterned photoresist to obtain a plurality of patterned electrodes 2, and then peeling off the photoresist to obtain a plurality of silicon nitride 1 modified with the electrodes 2;

[0128] After spin coating the surface of silicon nitride 1 with 20.0 wt% modified polypropylene resin in acetone solution to coat electrode 2, silicon nitride 1 / electrode 2 was placed in a drying oven at 80° C. for vacuum drying for 30 min to obtain a modified polypropylene resin layer;

[0129] A polycarbonate film with a thickness of 125 μm is attached to the modified polypropylene resin layer to form an adhesive layer 3;

[0130] A polydimethylsiloxane sheet with a thickness of 225 μm was used as a support layer 4 to adhere to the adhesive layer 3, and the material was transferred to a drying oven. The temperature of the drying oven was raised to 50° C. and kept warm for 12 minutes to obtain a silicon nitride 1 modified by a composite structure layer consisting of an electrode 2 / adhesion layer 3 / support layer 4;

[0131] The connection between the adhesion layer 3 and the silicon nitride 1 is washed with an acetone solution, and the composite architecture layer and the silicon nitride 1 are clamped with tweezers respectively, and the composite architecture layer is slowly lifted up until it is completely separated from the silicon nitride 1 to obtain the composite architecture layer.

[0132] S3. Preparation of short channel electrode tube

[0133] After the composite framework layer is cut into several required electrode materials, they are collected for later use, and a required electrode material is selected and one side of its support layer 4 is attached to a glass sheet, and the required electrode material is attached to the single crystal silicon 5 using a transfer table, and a pressure of 200 Pa is applied in the attached state, and the electrode material is heated to 120° C. and maintained for 5 minutes to obtain a target carrier modified with the electrode material;

[0134] The target carrier 5 modified with the electrode material is transferred to a solvent solution and soaked for 8 minutes. After peeling off the adhesion layer 3 and the support layer 4, a laminated structure consisting of the electrode 2 / target carrier 5 is obtained. The laminated structure is placed in an annealing machine, the annealing machine temperature is set to 160°C, and the annealing time is set to 3 hours to obtain a short channel transistor precursor;

[0135] Selecting a desired electrode material from the remaining electrode materials prepared in steps S1-S2;

[0136] Attach one side of the support layer 4 of the required electrode material to the glass sheet, position it just above the short-channel transistor precursor, and ensure the consistency of the distance between the required electrode material and the short-channel transistor precursor by accurately adjusting the Z-axis height of the transfer table;

[0137] The position of the transfer table in the x-axis and y-axis directions is adjusted to control the distance between the two electrodes of the required electrode material and the short-channel transistor precursor. When the distance reaches the requirement, the required electrode material is precisely bonded to the single crystal silicon 5 by using the transfer table. In the bonded state, a pressure of 300 Pa is applied to the new composite architecture layer, and it is heated to 100° C. and maintained for 5 minutes. During the process, a laser interferometer is used to measure and adjust the distance and angle between the required electrode material and the short-channel transistor precursor to obtain a modified short-channel transistor precursor.

[0138] The modified short channel transistor precursor was immersed in a dissolving solution for 8 minutes. After peeling off the adhesion layer 3 and the support layer 4, the material was placed in an annealing machine. The annealing machine temperature was set to 170° C. and the annealing time was set to 2 hours to obtain a short channel transistor.

[0139] Comparative Example 1

[0140] The difference between this comparative example and Example 3 is that step S1 is eliminated, and in step S2, 20.0 wt % acetone solution of polymethyl methacrylate is used in an equal amount to replace 20.0 wt % acetone solution of modified polypropylene resin.

[0141] Comparative Example 2

[0142] The difference between this comparative example and Example 3 is that in step S1, the modification step of the modified polypropylene resin precursor is eliminated, and in step S2, 20.0 wt % acetone solution of the modified polypropylene resin precursor is used in equal amount to replace 20.0 wt % acetone solution of the modified polypropylene resin.

[0143] Performance Test:

[0144] The width difference of the short channels in the short channel electrodes prepared in Examples 1-3 and Comparative Examples 1-2, as well as the average linear thermal expansion coefficient, transparency, leveling ability, adhesion grade and anti-scratch performance of the adhesion layer were tested.

[0145] The width difference of the bottom of the short channel is measured with reference to the standard GB / T 42158-2023 "Description and measurement method of micro-grooves and pyramidal needle structures in micro-electromechanical systems (MEMS) technology" to measure the maximum width and minimum width of the bottom of the short channel and calculate the width difference;

[0146] The average linear thermal expansion coefficient of the adhesive layer is determined according to the standard GB / T 36800.2-2018 "Thermomechanical analysis of plastics (TMA) Part 2: Determination of linear thermal expansion coefficient and glass transition temperature";

[0147] Transparency refers to the standard GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics" to measure the transparency of the adhesive layer after curing;

[0148] The leveling ability refers to the standard GB / T 33403-2016 "Test method for self-leveling performance of adhesives" to measure the height difference of the adhesion layer.

[0149] The adhesion grade is determined by referring to the standard GB / T 33049-2016 "Determination of Adhesion of Optical Thin Film Coatings for Polarizers" to determine the adhesion grade of the adhesive layer and other materials.

[0150] The scratch resistance performance refers to the standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels" to determine the scratch resistance level of the adhesive layer. The specific structure is shown in Table 1.

[0151] Table 1-Performance test data of each sample

[0152]

[0153] Data Analysis:

[0154] Comparative analysis of the data in Table 1 above shows that the short channel width difference of the short channel electrode prepared by the present invention is 0.2 μm, and the average linear thermal expansion coefficient (20-150°C) of the modified polypropylene resin prepared by the present invention is 42.4×10 -6 K -1 , the height difference of the layer after curing is 0.4mm, the adhesion level is 0, the transmittance is 96.4%, the scratch resistance level is 5, and all performances are better than the comparative example. The present invention combines the preparation of a modified polypropylene resin with a method for preparing a short channel transistor by mechanically stacking electrodes provided by the present invention. The high transparency and scratch resistance of the modified polypropylene resin ensure the accuracy of mechanical stacking, and its excellent leveling performance, high temperature resistance and adhesion performance ensure the stability of the electrode structure during the transfer process. The two are coordinated to reduce the preparation cost of the short channel transistor and improve its accuracy.

[0155] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0156] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0157] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a short channel transistor by mechanically stacking electrodes, characterized in that: The following steps are involved: S1, preparing a plurality of electrodes (2) on the surface of the substrate layer (1) after cleaning treatment; S2, arranging an adhesion layer (3) and a support layer (4) on the substrate layer (1) and the electrode (2) to obtain a substrate layer (1) modified with a composite framework layer; S3, peeling the composite structure from the substrate layer (1), and post-processing to obtain a plurality of electrode materials; S4, selecting the desired electrode material and transferring it to the surface of the target carrier (5), and post-processing to obtain a transistor material; S5. Continue to select the desired electrode material prepared in steps S1-S3 and transfer it to the surface of the target carrier (5) to obtain a short channel transistor.

2. A method for preparing a short channel transistor by mechanically stacking electrodes according to claim 1, characterized in that: In step S1, the cleaning process includes: using acetone, isopropyl alcohol and deionized water to clean the substrate layer (1) 3-5 times in sequence.

3. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 1, characterized in that: In step S1, the electrode (2) is processed by the following steps: A1, after spin coating a negative photoresist on the substrate layer (1), the substrate layer (1) is transferred to a drying oven at a temperature of 80° C. for vacuum drying to obtain a substrate layer (1) with the negative photoresist attached to the surface; A2. After adjusting the shape of the radiation area of ​​the photolithography machine, the photoresist is subjected to radiation exposure treatment to obtain a plurality of patterned photoresist surfaces of desired shapes; A3. Electron beam evaporation technology is used to perform surface deposition on the patterned photoresist surface. After deposition, the residual photoresist is stripped off to obtain an electrode (2).

4. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 1, characterized in that: In step S2, the method for forming the adhesive layer (3) and the support layer (4) comprises the following steps: B1. Spin-coating an adhesive solution on the surface of the substrate layer (1) to cover all the electrodes (2), and then transferring the material to a drying oven at a temperature of 80° C. for vacuum drying and keeping the temperature for 20-40 minutes to obtain a substrate layer (1) with an adhesive layer (3) attached to the surface; B2. Use a thin plate as a support layer (4) to adhere the adhesive layer (3), transfer the material to a drying oven, increase the temperature of the drying oven to 50° C., and keep it warm for 10-15 minutes to further obtain a composite structure layer consisting of electrode (2) / adhesive layer (3) / support layer (4).

5. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 4, characterized in that: In step B1, the adhesive solution is an acetone solution of 15-30wt% modified polypropylene resin, wherein the preparation method of the modified polypropylene resin is: 3-5 parts of 3-isocyanatepropyltrimethoxysilane, 8-10 parts of modified polypropylene resin precursor, 0.3-0.5 parts of triethylamine and 30-40 parts of dimethyl sulfoxide are weighed by weight and added into a reaction kettle, reacted at room temperature for 2-4h, and post-treated to obtain the modified polypropylene resin.

6. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 5, characterized in that: The preparation method of the modified polypropylene resin precursor is as follows: 3-5 parts of methyl methacrylate, 5-8 parts of 2-hydroxypropyl-1,2-phthalic acid-2-[(2-methyl-1-oxo-2-propenyl)oxy]ethyl ester, 0.3-0.5 parts of azobisisobutyronitrile and 30-40 parts of dimethyl sulfoxide are weighed by weight and added into a reaction kettle, the temperature of the reaction kettle is increased to 50-70° C., the reaction is kept warm for 2-4 hours, and the modified polypropylene resin precursor is obtained by post-treatment.

7. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 1, characterized in that: In step S3, the method for peeling the composite structure layer is: using a chemical reagent to flush the connection between the adhesive layer (3) and the substrate layer (1), using tweezers to clamp the composite structure layer and the substrate layer (1) respectively, and slowly lifting the composite structure layer until it is completely peeled off from the substrate layer (1).

8. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 1, characterized in that: In step S4, the method for transferring the electrode material is as follows: attach one side of a support layer (4) of a desired electrode material to a glass sheet, use a transfer table to attach the electrode material to a target carrier (5), apply a pressure of 200-400 Pa in the attached state, and heat to 120-150° C. for 5-10 minutes to obtain a target carrier (5) modified with the electrode material.

9. The method for preparing a short channel transistor by mechanically stacking electrodes according to claim 1, characterized in that: In step S5, the short channel transistor is obtained by processing the following steps: D1. Select a desired electrode material from the remaining electrode materials prepared in steps S1-S3, attach one side of the support layer (4) of the desired electrode material to a glass sheet, position it just above the short-channel transistor precursor, and precisely adjust the Z-axis height of the transfer table to ensure consistency of the distance between the short-channel transistor precursor and the desired electrode material; D2, adjusting the position of the transfer table in the x-axis and y-axis directions to control the distance between the two electrodes of the desired electrode material and the short-channel transistor precursor. When the distance reaches the requirement, the desired electrode material is accurately bonded to the target carrier (5) using the transfer table. In the bonded state, a pressure of 300-500 Pa is applied to the new composite architecture layer, and the layer is heated to 100-150° C. for 5-10 minutes. During the process, a laser interferometer is used to measure the distance and angle between the desired electrode material and the short-channel transistor precursor to obtain a modified short-channel transistor precursor. D3. Soak the modified short channel transistor precursor in a dissolving solution for 5-10 minutes. After peeling off the adhesion layer (3) and the support layer (4), put the material into an annealing machine. The annealing machine temperature is set to 150-170° C. and the annealing time is set to 1-3 hours to obtain a short channel transistor.

Citation Information

Patent Citations

  • Method for carrying out electrode transfer by using fluorine crystal mica

    CN116581021A

  • Process for the production of modified polyolefin

    US4146529A

  • Single-layer-electrode type charge coupled device having double conductive layers for charge transfer electrodes

    US6165908A